2018
DOI: 10.1111/gcb.14118
|View full text |Cite
|
Sign up to set email alerts
|

Woody encroachment slows decomposition and termite activity in an African savanna

Abstract: Woody encroachment can lead to a complete switch from open habitats to dense thickets, and has the potential to greatly alter the biodiversity and ecological functioning of grassy ecosystems across the globe. Plant litter decomposition is a critical ecosystem process fundamental to nutrient cycling and global carbon dynamics, yet little is known about how woody encroachment might alter this process. We compared grass decay rates of heavily encroached areas with adjacent nonencroached open areas in a semi-arid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 56 publications
8
26
0
Order By: Relevance
“…It seems the decomposition rates associated with active Macrotermes mounds are not dependent on moisture, consistent with Veldhuis et al (2017). On a larger scale, Leitner et al (2018) showed that shade, resulting from increasing tree cover, was associated with reduced decomposition. This was attributed to reduced termite activity in the wooded areas.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…It seems the decomposition rates associated with active Macrotermes mounds are not dependent on moisture, consistent with Veldhuis et al (2017). On a larger scale, Leitner et al (2018) showed that shade, resulting from increasing tree cover, was associated with reduced decomposition. This was attributed to reduced termite activity in the wooded areas.…”
Section: Discussionsupporting
confidence: 54%
“…On a larger scale, Leitner et al. () showed that shade, resulting from increasing tree cover, was associated with reduced decomposition. This was attributed to reduced termite activity in the wooded areas.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, on both agricultural and pastoral land-uses in drier regions, macrodetritivore communities were able to sustain recalcitrant litter decomposition during periods of water scarcity. Continued macrodetritivore foraging during the dry season has been observed in other tropical ecosystems Jouquet et al 2011;Veldhuis et al 2017), but is not exhibited by all savannah macrodetritivore species (Davies et al 2015;Davies et al 2013;Leitner et al 2018). In contrast, litter decomposition by microbes and microdetritivores in our study was constrained by regional and seasonal water availability across all land-use types, as also seen in other tropical ecosystems (Anaya et al 2012;Becker and Kuzyakov 2018;Ngatia et al 2014).…”
Section: Discussionsupporting
confidence: 57%
“…This, in turn, could further constrain decomposition by microbes and negatively influence macrodetritivores that would seek moist refuges and minimise foraging due to higher risk of desiccation (Cornelius and Osbrink 2010;Joly et al 2019;Woon et al 2019). Additionally, dry season foraging is not a universal trait to all litter feeding macrodetritivore species, and several termite and isopod species are seemingly dormant during the dry season months resulting in little or no litter foraging (Davies et al 2015;Davies et al 2013;Leitner et al 2018). As such, there remains ambiguity over the contribution of macrodetritivores to litter decomposition across temporally and spatially variable rainfall in tropical savannah ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Europe is the continent with the lowest percentage of land with stable 31 productivity levels in PAs (38%) and with the largest share of protected land with increasing land 32 productivity (32%), which may be related to the high population density and share of agricultural 33 land within PAs as well as to rural land abandonment processes in many regions of Europe. In 34 conclusion, we provide a relevant indicator and assessment of land productivity dynamics that 35 contributes to characterise the state, pressures and changes in and around protected areas 36 globally. Further research may focus on more detailed analyses to disentangle the relative 37 contribution of specific drivers (from climate change to land use change) and their interaction 38 with land productivity dynamics and potential land degradation in different regions of the world.…”
mentioning
confidence: 99%